2021
DOI: 10.1001/jamaneurol.2021.3723
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Increased Seizures During Rewarming After Hypothermia for Neonatal Hypoxic Ischemic Encephalopathy and Abnormal Neurodevelopmental Outcomes at 2-Year Follow-up

Abstract: IMPORTANCECompared with normothermia, hypothermia has been shown to reduce death or disability in neonatal hypoxic ischemic encephalopathy but data on seizures during rewarming and associated outcomes are scarce. OBJECTIVE To determine whether electrographic seizures are more likely to occur during rewarming compared with the preceding period and whether they are associated with abnormal outcomes in asphyxiated neonates receiving hypothermia therapy. DESIGN, SETTING, AND PARTICIPANTSThis prespecified nested co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 65 publications
(80 reference statements)
1
16
0
2
Order By: Relevance
“…HIE-associated seizures have typical onset and maximum seizure burden within 24 h after birth ( 61 ). Therapeutic hypothermia reduces seizure burden, but nearly half of the cooled babies still have seizures, and the odds of seizures during rewarming are higher ( 62 ). The incidence of seizures in preterm infants is much higher than term infants ( 63 ).…”
Section: Introductionmentioning
confidence: 99%
“…HIE-associated seizures have typical onset and maximum seizure burden within 24 h after birth ( 61 ). Therapeutic hypothermia reduces seizure burden, but nearly half of the cooled babies still have seizures, and the odds of seizures during rewarming are higher ( 62 ). The incidence of seizures in preterm infants is much higher than term infants ( 63 ).…”
Section: Introductionmentioning
confidence: 99%
“…B. für Früh- und Neugeborene mit zerebralen Anfällen und nach perinataler Asphyxie empfohlen. Die Ableitung sollte bis nach dem Ende der Aufwärmphase fortgeführt werden, da in dieser Phase noch prognostisch ungünstige, oft subklinische, Anfällen auftreten können [ 17 ]. Bei neonatalem Schlaganfall und Sinusvenenthrombose, aber auch bei unklaren neurologischen Symptomen empfiehlt sich der Einsatz ebenfalls.…”
Section: Amplitudenintegriertes Elektroenzephalogrammunclassified
“…60) Of note, many studies reported a high incidence of seizures during cooling and rewarming periods in cooled HIE newborns. 24,6365) Interestingly, Chalak et al 66) found a higher seizure burden during rewarming and worse longterm outcomes at 2 years of age and highlighted the importance of continuous EEG 44,71) Two recent studies showed no significant difference between phenobarbital and levetiracetam as 1st line in treatment of electrical seizures 72,73) while, one study showed superiority of phenobarbital 44) Levetiracetam 1st or 2nd line of treatment Effects: better neurodevelopmental out come 44,74,75) ; antiepileptogenic effect 76) ; less reported adverse effects of pheno barbital 77) 35%-86% seizure control 78,79) Phenytoin 1st or 2nd line of treatment S/E: cardiac arrhythmia, hepatoxic 45% seizure control 80) Midazolam 2nd or 3rd line of treatment S/E: hypotension, respiratory depres sion…”
Section: Outcomementioning
confidence: 99%
“…Abnormal outcome had been scored if TSB and MSB exceeding 40 and 13 minutes respectively Seizures burden alone is a predictor of poor outcome Prolonged or recurrent sei zures 67) Each 10minute increase in seizure burden is associated with a 5fold risk increase of epilepsy, while having more than 10 seizures increases the risk of epilepsy by 30fold compared to no seizures Seizure burden during re warming 66) High seizure burden during rewarming after 72 hours of cooling compared to 120 hours of cooling normal EEG findings were associated with poor response in an additional study, which also identified higher mean seizure score and higher degrees of brain magnetic resonance imaging injury (white matter, cortex, and watershed regions) were associated with a poor response to phenobarbital. 70) Briefly, the early declaration of this silent enemy is vital through the early use of EEG in any suspected or critically ill newborn with the aim of detecting any abnormal discharge and initiating antiepileptic drugs in curable doses that dampen the current and subsequent sparks.…”
Section: Variablementioning
confidence: 99%
See 1 more Smart Citation